O acesso à internet como instrumento otimizador de direitos fundamentais - Paula, Víctor Augusto Lima de (2014)
The emergence of Internet and its gradual propagation in modern society brought along a factual revolution in human interactions, echoing in the most diverse ways, even though this technology is not yet accessible to everyone around the globe. Among these reverberations, the juridical and political ones nowadays evoke and trigger important discussions in national and international scope about Internet access juridical status. For instance, it is inquired if that access can be considered a human right or a constitutional fundamental right, how public policies and international agendas can guarantee an access free of state interference and how to bring access to everyone. This research, through qualitative analysis of national and foreign works and documents, addresses these contemporary questions and aims to unveil the juridical nature of Internet access, considering the optimization interfaces and correlations between this access and the fundamental rights, mainly those related to the exercise of freedom of speech, to the concretion of the social right to education and to the protection and fortification of Democracy.